Drilling Technology - Tolouei-Rad, Majid (IntechOpen, 2021)
Drilling is an old and well-known operation, and over the years significant improvements have been achieved in the performance of drilling operations. This book presents the latest findings of scientists and engineers for enhancing the quality and performance of drilling in various industries. It covers interesting topics on conventional and multi-spindle drilling operations, challenges of machining widely used aluminum alloys, non-conventional drilling using the hybrid EDM+ECM method, development of CNC machines, and the loss of circulation in the drilling of oil wells. This book is a useful resource for engineers, researchers, students, and those who work in industries involved in various forms of drilling operations.